Study on evolution process of water inrush disaster of tunnel based on the distinct element method. Issue 7 (October 2021) - Jing, Fu; Xiuli, Ding; Hui, Fu; Shuling, Huang; Jun, He; Zhipeng, Xiang
Abstract: On the basis of the analysis of the geological characteristics of the construction adit of a water diversion project, in conjunction with the phenomena of water gushing, mud bursting and collapse encountered in the construction process of the tunnel, the fracture network model of the typical rock mass in the project area is established. Based on the seepage stress coupling mechanism of the fractured rock mass, the UDEC discrete element method is used to analyze the gradual development process of the surrounding rock fractures in the excavation process of the tunnel. The dynamic evolution law of tunnel water inrush is revealed, which could provide a good reference for the safe construction of underground engineering in water rich area and the design and control of surrounding rock stability.